SPGCam: A specifically tailored camera for solar observations - Orozco Suárez, David; Álvarez García, Daniel; López Jiménez, Antonio C.; Balaguer Jiménez, María; Hernández Expósito, David; Labrousse, Pierre; Bailén, Francisco J.; Bustamante Díaz, Isabel; Bailón Martínez, Eduardo; Aparicio del Moral, Beatriz; Morales Fernández, José M.; Sánchez Gómez, Antonio; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Designing a new astronomical instrument typically challenges the available cameras on the market. In many cases, no camera can fulfill the requirements of the instrument in terms of photon budget, speed, and even interfaces with the rest of the instrument. In this situation, the only options are to either downgrade the performance of the instrument or design new cameras from scratch, provided it is possible to identify a compliant detector. The latter is the case of the SPGCams, the cameras developed to be used with the Tunable Magnetograph (TuMag) and the Sunrise Chromospheric Infrared spectroPolarimeter (SCIP) for the Sunrise iii mission. SPGCams have been designed, developed, and built entirely in-house by the Solar Physics Group (SPG) at the Instituto de Astrofísica de Andalucía (IAA-CSIC). We report here on the scientific rationale and system engineering requirements set by the two instruments that drove the development, as well as on the technical details and trade-offs used to fulfill the specifications. The cameras were fully verified before the flight, and results from the assembly and verification campaign are presented as well. SPGCams share the design, although some parametric features differentiate the visible cameras (for TuMag) and the IR ones (for SCIP). Even though they were specifically developed for the Sunrise iii mission, the robust and careful design makes them suitable for different applications in other astronomical instruments.